2023
DOI: 10.3390/foods12071380
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo Shoots Modulate Gut Microbiota, Eliminate Obesity in High-Fat-Diet-Fed Mice and Improve Lipid Metabolism

Abstract: Bamboo shoots (BS) have a variety of nutritional benefits; however, their anti-obesity effect and its underlying mechanism of action are still unclear. In this study, we investigated the protective effect of BS against high-fat diet (HFD)-induced gut dysbiosis in mice. After 12 weeks of feeding C57BL/6J mice either on a normal or an HFD with or without BS, metabolic indicators, including blood lipids and glucose tolerance, were measured. 16S rRNA gene sequencing and metabolomics were used to identify alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…30,31 In contrast, Blautia and Faecalibaculum have been documented to show a positive association with obesity and impaired glucose tolerance. 32 The results at the species level were consistent with those observed at the corresponding genus level. These findings suggested that ACN from Lycium ruthenicum Murray exerts its anti-obesity effect on female mice through the regulation of the gut microbiota, specifically by increasing the abundances of beneficial bacteria such as Allobaculum, Lactobacillus_johnsonii and Lactobacillus_reuteri within Firmicutes.…”
Section: Discussionsupporting
confidence: 83%
“…30,31 In contrast, Blautia and Faecalibaculum have been documented to show a positive association with obesity and impaired glucose tolerance. 32 The results at the species level were consistent with those observed at the corresponding genus level. These findings suggested that ACN from Lycium ruthenicum Murray exerts its anti-obesity effect on female mice through the regulation of the gut microbiota, specifically by increasing the abundances of beneficial bacteria such as Allobaculum, Lactobacillus_johnsonii and Lactobacillus_reuteri within Firmicutes.…”
Section: Discussionsupporting
confidence: 83%
“…A previous study found that another omnivorous animal, lizard individuals, also harbored significantly more Methanobrevibacter [49]. Muribaculaceae, a short-chain fatty acid (SCFA)-producing bacteria [50], was associated with a high-fat diet and has been demonstrated in piglets [51]. Paludibacteraceae was another abundant family in the marmot, and it was connected with low protein and branched-chain amino acids in pigs [52].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated the protective roles of the supplements on gut microbiota dysbiosis in aging mice. At genus levels, norank_f__Muribaculaceae 36) , Lactobacillus 37) , unclassified_f__Lachnospiraceae, norank_f__Lachnospiraceae 38) , Lachnospiraceae_ UCG-006 39) , Alistipes 40) , Streptococcus 41) , Rikenellaceae_ RC9_gut_group 42) , unclassified_f__Prevotellaceae 43) are SCFAs-producing bacteria, which are beneficial for liver health and are reported to be negatively associated with hepatic oxidative stress, inflammation and damage 44) . Norank_f__norank_o__Clostridia_UCG-014 45) , and Pre-votellaceae_UCG-001 46) are beneficial bacteria, that are reported to exert anti-inflammatory function and are inversely correlated with pro-inflammatory cytokines, like IL-6 and TNF-α.…”
Section: Discussionmentioning
confidence: 99%